The addition of yerba mate leaves on bread dough has influences on fermentation time and the availability of phenolic compounds?. (July 2021) - Santetti, Gabriela Soster; Dacoreggio, Marina Volpato; Inácio, Heloisa Patrício; Biduski, Barbara; Hoff, Rodrigo Barcellos; Fritzen Freire, Carlise Beddin; Gutkoski, Luiz Carlos; Amboni, Renata Dias de Mello Castanho
Abstract: This study investigated the effect of different fermentation times of dough made with whole wheat flour (WWF) added with yerba mate (YM), and the effect on rheological behavior, release of phenolic compounds, and antioxidant activity. Three treatments were evaluated: YM1 (2.5%; w/w), YM2 (4.5%; w/w), and the control sample (0%). The dough fermentative behavior showed an alteration in CO2 production, and dough volume was reduced in the presence of YM. The addition of YM, together with the fermentation process, increased the free, bound, and total phenolic content, as well as the antioxidant activity of the dough. The addition of 4.5% of YM showed higher content for free phenolic compounds on the dough after the fermentation. 26 phenolic compounds were identified in the dough samples. Rutin was the main compound in doughs with YM, comprising 79% and 61% of total phenolic content of YM2 and YM1, respectively. The phenolic profile demonstrated that fermentation times of 30 and 60 min released greater amounts of compounds in the three studied doughs, mostly caffeic acid, ferulic acid, chlorogenic acid, p -coumaric acid, isoquercetin, and rutin. These results suggest that the dough fermentation process may be a determining factor for the release of phenolic compounds. Graphical abstract: Image 1 Highlights: Yerba mate modified the rheological characteristics of dough fermentation. The most effective fermentation times to release phenolics were 30 and 60 min. 26 phenolic compounds of different classes were identified in the bread dough. Yerba mate has potential benefits in human consumption.